Imagining The Real - Grant, R. author. aut Link
XVI, 248 p.
Keywords: Throughout its ten related essays, Imagining the Real contrasts our abstract imaginings about the human world with the imaginative insights provided by art and experience. It questions, variously, the relevance of game theory and sociobiology to politics; the supposed intrinsic values of liberal freedom, cultural change, and democratic action; and the claims of Marxism, deconstruction and 'Theory' generally to be non-ideological. More positively, it reinterprets fiction as a specific invitation to imagine, and celebrates Shakespeare, L.H. Myers and Beckett as truly critical, because truly imaginative, exponents of ideas.